2019
DOI: 10.4236/pp.2019.103013
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Multi-Component Quantitation of Cortex Moutan and Its Intestinal Absorption Characteristics

Abstract: Cortex Moutan (Paeonia suffruticosa Andr.) is a common traditional Chinese medicine and has been widely used in clinic for 2000 years in China. As sources for this crude drug are always mixed with other species, many cultivars on herbal market may lead to quality instability. Multi-component quantitative analysis is an efficient method to reflect chemical profiles of herb medicine and is always taken as the main method for quality evaluation. So, the aim of this work is to develop analytical method to quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…In addition, peaonol, paeoniflorin and their derivatives were the representative components of monoterpene glycosides and phenols (Zhou and Lv, 2008; Wang P. et al, 2017;Wang Z. Q. et al, 2017). In the present study, we found peaonol and paeoniflorin were the main components and account for 80% contents of the total detected components, which were in accordance with our previous study (Ge et al, 2019). However, the chemical properties of MCs from herbal market showed great diversities, in which the contents of peaonol and paeoniflorin ranged from 13.85 to 26.08 mg/g and 3.95-14.31 mg/g, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, peaonol, paeoniflorin and their derivatives were the representative components of monoterpene glycosides and phenols (Zhou and Lv, 2008; Wang P. et al, 2017;Wang Z. Q. et al, 2017). In the present study, we found peaonol and paeoniflorin were the main components and account for 80% contents of the total detected components, which were in accordance with our previous study (Ge et al, 2019). However, the chemical properties of MCs from herbal market showed great diversities, in which the contents of peaonol and paeoniflorin ranged from 13.85 to 26.08 mg/g and 3.95-14.31 mg/g, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In previous study, we found paeonol, paeoniflorin, benzoylpaeoniflorin, paeonolide, gallic acid and oxypaeoniflorin (Supplementary Figure S1) which were the predominant components in MC, and the quantitative analytical method with simultaneously quantifying the six ingredients in MC was established (Ge et al, 2019). Briefly, The HPLC analyses were performed using a LC-20A liquid chromatography system (Shimadzu Co., Japan) and samples were separated on an Ecosil C 18 (250 mm × 4.6 mm, 5 μM, Lubex Co., China).…”
Section: Quantification Of Six Main Components In Moutan Cortexmentioning
confidence: 99%